(untitled) (NAU Journal of Technology and Vocational Education, 2026)
The study assessed the application of innovative practices by Business Educators for improving the teaching of accounting courses in universities in South East Nigeria. Descriptive survey design was adopted for the study. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The population consisted of 123 Business Educators in universities in South-East, Nigeria. Census sampling method was used because the population is of a manageable size. The instrument for data collection was a structured questionnaire developed by the researcher. Cronbach alpha was used to ascertain the reliability of the instrument with overall co-efficient of 0.85. Mean and standard deviation were used to answer the research questions while t-test was used to test the hypotheses at a 0.05 level of significance. The findings revealed that Business Educators agreed that application of project-based and service learning improves the teaching of accounting courses in universities in South East, Nigeria. Based on the findings, the study concluded that the extent this program achieves its noble objectives depends to a large extent on the quality and competencies possessed by the Business Educators as well as the innovative skills they apply to facilitate effective teaching of accounting courses. It was recommended among others that Business Educators should acquire the requisite skill towards adoption and utilization of project-based and service learning for effective teaching and learning process.